Prioritization of genetic variants predisposing to coronary heart disease in the Bulgarian population using centenarian exomes. Issue 1 (1st January 2019) - Ganev, Mihail; Balabanski, Lubomir; Serbezov, Dimitar; Karachanak-Yankova, Sena; Vazharova, Radoslava; Nesheva, Desislava; Hammoudeh, Zora; Nikolova, Dragomira; Antonova, Olga; Staneva, Rada; Mihaylova, Marta; Damyanova, Vera; et al.
Abstract: Coronary heart disease (CHD) is a major cause of mortality and morbidity in Europe. CHD is usually caused by atherosclerosis. Despite extensive studies that have identified a large number of genetic variants, strong evidence of association with CHD are not easily replicable in different populations. Two DNA pools were constructed: one with 32 Bulgarian centenarians and one with 61 young healthy Bulgarian individuals. The pools were whole-exome sequenced and variants were annotated and quality filtered (89, 810 filtered variants). Allele frequencies were estimated and Fisher's exact test was used to evaluate the significance of allele frequency differences between the two pools. Two publicly available databases, Ensembl and DisGeNET, were used as a source of 2025 CHD-associated variants (CHD-AVs). These single nucleotide polymorphisms were screened in our data and 158 variants in 133 genes were found. ToppGene pathways analysis of genes called in both pools discovered participation of 37 genes in 9 significantly over-represented pathways. Eight variants in these 37 genes have significantly higher frequency in young individuals, and are nominated for CHD association. Variants called only in the young individuals pool (13 variants) are also nominated for association with CHD. Based on sufficiently unambiguous literature data, from the nominated variants, we prioritize five as associated with CHD in the studied Bulgarian sample. Centenarian genomes can be used to provide additional information regarding the clinical relevance of genetic variants reported as associated with CHD.